Analysis of Total Productive Maintenance (TPM) Using Overall Equipment Effectiveness on Jigger Machine at PT. Indo Porcelain, Tangerang - Akbar, Muhammad; Abdillah, Hamid (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Indo Porcelain is a industry engaged in manufacturing that produces products such as plates and glasses. During the production process PT. Indo Porcelain often experiences considerable downtime. The purpose of this study is to analyze Total Productive Maintenance (TPM),OEE,and working hours of the jigger machine. The results of the analys show that the OEE value of the jigger machine at PT. Indo Porcelain does not meet the international standards set. Caused by old machines, long maintenance procedures and a long maintenance process.